SIgA, TGF-β1, IL-10, and TNFα in Colostrum Are Associated with Infant Group B Streptococcus Colonization - Le Doare, Kirsty; Bellis, Katie; Faal, Amadou; Birt, Jessica; Munblit, Daniel; Humphries, Holly; Taylor, Stephen; Warburton, Fiona; Heath, Paul T.; Kampmann, Beate; Gorringe, Andrew (Frontiers in Immunology, 2017)
Background: Group B Streptococcus is a major cause of mortality and morbidity in infants and is associated with transmission from a colonised mother at birth and via infected breastmilk. Although maternal/infant colonisation with Group B Streptococcus (GBS) is common, the majority of infants exposed to GBS remain unaffected. The association between breastmilk immune factors and infant colonisation and disease prevention has not been elucidated. Objectives: We have investigated the association between SIgA and cytokines in breastmilk and infant GBS colonisation and clearance. Methods: Mother/infant GBS colonisation was determined in a prospective cohort of 750 Gambian mother/infant pairs followed to day 90 of life. Anti-GBS secretory IgA bound to the surface of whole bacteria was assessed by flow cytometry and a panel of 12 cytokines quantified by mesoscale discovery in colostrum, breastmilk and serum. Results: Compared with infants receiving low anti-GBS SIgA in colostrum, infants receiving high anti-GBS SIgA were at decreased risk of GBS colonisation for serotypes III and V. Infants colonised at day 6 were twice as likely to receive colostrum with high TGF- β1, TNFα, IL10 and IL-6 compared to uncolonised infants. Infants receiving high colostral TGF- β1, TNFα and IL-6 had two-fold enhanced GBS clearance between birth and day 90. Conclusion: Our results suggest that the infant GBS colonisation risk diminishes with increasing anti-GBS SIgA antibody in breastmilk and that key maternally-derived cytokines might contribute to protection against infant colonisation. These findings might be leveraged to develop interventions including maternal vaccination that may reduce infant GBS colonisation.